Iron in Glacial Systems: Speciation, Reactivity, Freezing Behavior, and Alteration During Transport - Raiswell, Robert; Hawkings, Jon; Elsenousy, Amira; Death, Ros; Tranter, Martyn; Wadham, Jemma (Frontiers in Earth Science, 2018)
A more insightful view of iron in glacial systems requires consideration of iron speciation and mineralogy, the potential for iron minerals to undergo weathering in ice-water environments, the impact of freezing on concentration and speciation, and potential for glacial delivery to undergo alteration during transport into the ocean. A size fractionation approach improves recognition of iron speciation by separating dissolved Fe (<0.2 or <0.45 μm) into soluble Fe (<0.02 μm) and colloidal/nanoparticulate Fe (0.02 to 0.2 or 0.45 μm). The ranges of soluble Fe concentrations in icebergs and meltwaters are similar (tens of nanomolar). The range of colloidal/nanoparticulate Fe concentrations in icebergs are an order of magnitude higher (hundreds of nanomolar) and up to thousands of nanomolar in meltwaters. The importance of particulate iron speciation in glacial sediments is also recognized by using carefully calibrated sequential extractions with ascorbic acid (FeA comprising fresh ferrihydrite which is potentially bioavailable) and dithionite (FeD comprising all remaining (oxyhydr)oxide Fe). Iceberg and glacier sediments contain lower concentrations of FeA (0.032 ± 0.024 and 0.042 ± 0.059 wt. %) than meltwater suspended sediments (FeA 0.12 ± 0.09 wt. %). Glacier sediments also contain low concentrations of FeD (0.060 ± 0.036) but concentrations of FeD are comparable in iceberg and meltwater sediments (0.38 ± 0.24 wt. % compared to 0.31 ± 0.09 wt.%). Reactions in ice-water systems produce potentially bioavailable Fe(II) and ferrihydrite by pyrite oxidation, iron mineral dissolution (aided by low pH and organic complexes) and reduction (aided by UV radiation). Some icebergs contain high concentrations of FeA (>0.1 wt. %) which represent samples in which the on-going transformation of ferrihydrite to goethite/hematite is incomplete. Numerical models of freezing in subglacial systems show that the nanomolar levels of soluble Fe in icebergs cannot be achieved solely by freezing, and must indicate the presence of nanoparticulate Fe and/or iron desorbed from ice or sediments during melting. Models of freezing effects in sea ice show that nanomolar levels of soluble Fe are achievable because high concentrations of hydroxide and chloride ions maintain dissolved iron as soluble complexes. Delivery of iron through fjords is temporally and spatially variable due to circulation patterns, mixing of different sources, and aggregation through salinity gradients.